FGFR3 signaling induces a reversible senescence phenotype in chondrocytes similar to oncogene-induced premature senescence - Krejci, Pavel; Prochazkova, Jirina; Smutny, Jiri; Chlebova, Katarina; Lin, Patricia; Aklian, Anie; Bryja, Vitezslav; Kozubik, Alois; Wilcox, William R (Bone, 2010)
Oncogenic activation of the RAS-ERK MAP kinase signaling pathway can lead to uncontrolled proliferation but can also result in apoptosis or premature cellular senescence, both regarded as natural protective barriers to cell immortalization and transformation. In FGFR3-related skeletal dyplasias, oncogenic mutations in the FGFR3 receptor tyrosine kinase cause profound inhibition of cartilage growth resulting in severe dwarfism, although many of the precise mechanisms of FGFR3 action remain unclear. Mutated FGFR3 induces constitutive activation of the ERK pathway in chondrocytes and, remarkably, can also cause both increased proliferation and apoptosis in growing cartilage, depending on the gestational age. Here, we demonstrate that FGFR3 signaling is also capable of inducing premature senescence in chondrocytes, manifested as reversible, ERK-dependent growth arrest accompanied by alteration of cellular shape, loss of the extracellular matrix, upregulation of senescence markers (alpha-GLUCOSIDASE, FIBRONECTIN, CAVEOLIN 1, LAMIN A, SM22alpha and TIMP 1), and induction of senescence-associated beta-GALACTOSIDASE activity. Our data support a model whereby FGFR3 signaling inhibits cartilage growth via exploiting cellular responses originally designed to eliminate cells harboring activated oncogenes.
Keywords: signální transdukce; Signal Transduction; Extracellular Signal-Regulated MAP Kinases; tvar buňky; stárnutí buněk; Extracellular Matrix; onkogeny; Receptor, Fibroblast Growth Factor, Type 3; receptor fibroblastových růstových faktorů, typ 3; Phenotype; krysa rodu Rattus; extracelulární matrix; zvířata; proliferace buněk; Oncogenes; chondrocyty; apoptóza; Cell Shape; Cell Proliferation; fenotyp; Rats; extracelulárním signálem regulované MAP kinasy; Cellular Senescence; Animals; Chondrocytes; Apoptosis